Deposition of ZnO-Al (AZO) thin films for optical properties - Hussin, R.; Anuar, S. Z. S.; Ibharim, S. A.; Kamdi, Z.; Ainuddin, A. R.; Harun, Z. (2021)
Zinc Oxide (ZnO) is an inorganic compound and it is doped with aluminum to increase its capabilities. Aluminum Zinc Oxide (AZO) thin films are semiconductor materials that have band gap energy of 3.3eV. Various method of deposition have been study to growth AZO thin films. It has been extensively use in solar cell application, display application, gas sensing purposes, and thin film transistors (TFTs). In this work, sol gel method and spin coating was used to deposited AZO thin films. The ZnO sol-gel were synthesized using zinc acetate dihydrate as precursor, isopropanol as solvent, diethanolamine as sol stabilizer, and distilled water as oxidation agent. Then, synthesized ZnO were doped with different mole ratio of aluminum nitrate nanohydrate to produced AZO. The glass substrate was used as substrate and AZO thin films were then calcinated at 300°C and 500°C. The characterization of AZO thin film were done using X-ray Diffraction (XRD), Atomic Force Microscopy (AFM), Ultraviolet-visible spectroscopy (UV-Vis), Field Emission Scanning Electron Microscope (FESEM), and Energy Dispersive X-ray spectroscopy (EDX). The XRD results show that the ZnO with hexagonal wurtzite-type structure and temperature does have effect on the film intensity which related to crystallinity of thin films. Through AFM analysis, the value of RMS decreases from 3.018 nm to 2.240 nm as the temperature increases. Meanwhile, from UV-Vis result, it can be seen that AZO thin film have a high transmittance percentage above 90% after wavelength 400 nm with band gap value of 3.3 eV. FESEM image show that the grain boundary of AZO decrease with both parameter (mole ratio and calcinations temperature). Both parameters do have effect on AZO thin film. EDX analysis shows that there are existence of zinc, oxide, and aluminum.